Duodenal mucosal damage in 31 infants with gastroenteritis - Barnes, G. L. (1973)
Duodenal biopsies taken in the acute stage of gastroenteritis in 31 infants have shown histological abnormality and disaccharidase depression in the majority. In 5, mucosal damage was severe with changes similar to those seen in coeliac disease. Repeat biopsies in 3 of these showed marked improvement after 3 days, 8 days, and 7 weeks, respectively. Persisting sugar intolerance occurred in approximately 50% of patients under 6 months of age, but this complication bore no relation to disaccharidase depression in the acute stage of the illness.